MENGUKUR KUALITAS PELAYANAN TENAGA PENJUALAN: STUDI PADA SEBUAH PERUSAHAAN DISTRIBUTOR SANDAL KARET DI SURABAYA - Marhaeni, Novie Prasetyaning; Anindita, Nathania Etsa (Politeknik Ubaya, 2024)
Over the past three years, the sales of sandals and rubber shoes have been significantly impacted by the global COVID-19 pandemic. This has coincided with the economic downturn, particularly in the industrial sector. One way to recover is through innovations in the sales of primary, secondary, and tertiary products. By providing high-quality services and prime performance from the human resources possessed, it is hoped that the company's performance can be improved. The purpose of this study is to understand the quality of service and sales performance. The method used in this study is a qualitative descriptive approach, where data collection was conducted through interviews, observations, and recordings. Through a literature review and the information obtained, it was found that the service provided by the salespeople being studied has an impact on their performance. The factors studied include product knowledge, clarity in presenting information, and the process of providing service quickly, accurately, and completely. Many studies on customer service quality have been conducted in service companies such as banks, hotels, and hospitals, but there have been few assessments of service quality in small industries with standardized service standards. The purpose of this study is to bridge this gap by evaluating the condition of service quality for customers to formulate effective and suitable strategies for improving the company. The limitations of this study are that it only focuses on one distributor company and additional approaches are needed to obtain more complex information.